METODOLOGI PENULISAN SUNAN AL-TURMUZ}I - Barsihannor, Barsihannor (Rihlah: Jurnal Sejarah dan Kebudayaan, 2018)
Ima>m al-Turmuz}i is a famous Islamic scholar in hadits area who has collected hadits in his book called Sunan al-Turmudzi. In addition, he also released many written works that we are still able to read and study parts of them for the moment. Imam al-Turmuzi has got many appreciations from Islamic scholars either in the form of comment or praise because of his hadits which are considered having good standard and quality. Some Islamic scholars, however, criticize his book for including several d}a>if hadits. Imam al-Turmu>z}i wrote terminology abwa>b and ba>b in its collation methodology.  He also introduced the terminology hadits hasan in his book al-Ja>mi.